Effects of an individualised nutritional intervention to tackle malnutrition in nursing homes: a pre-post study - Seemer, Johanna; Kiesswetter, Eva; Fleckenstein-Sussmann, D.; Gloning, M.; Bader-Mittermaier, S.; Sieber, Cornel; Sixt, B.; Wurm, S.; Volkert, Dorothee (European Geriatric Medicine, 2021)
Purpose: Individualised interventions are recommended to tackle malnutrition in older adults, but approaches for nursing home (NH) residents are scarce. This study investigated the effects of an individualised nutritional intervention in NH residents with (risk of) malnutrition. Methods: In a pre-post study, 6 weeks (w) of usual care were followed by 6w of intervention. The intervention consisted of up to three supplement modules (sweet and savoury protein creams and protein-energy drink, single or combined) and, if required, reshaped texture-modified meals (RTMM). Results: Fifty residents completed the study (84 ± 8 years, 74% female). One-third (32%) received RTMM. Additional 258 ± 167 kcal/day and 23 ± 15 g protein/day were offered. Mean daily energy intake increased by 207 (95%CI 47–368, p = 0.005) kcal and protein intake by 14 (7–21, p < 0.001) g (w12 vs w1). Quality of life (QoL) increased in the subscale “care relationship” (+ 9 (3–15) points, p = 0.002, w12 vs w6). Body weight, handgrip strength, and other QoL subscales did not change. Conclusion: Our intervention improved dietary intake and one QoL subscale in NH residents with (risk of) malnutrition. As a next step, randomized controlled trials are needed to investigate the impact of individualised interventions more comprehensively.
CRIS-Team Scopus Importer:2021-12-10
Keywords: Energy intake; Food supplements; Individualised; Malnutrition; Nursing home; Nutritional intervention